SEPARATION OF PATCHOULI ALCOHOL FROM PATCOULI OIL BY FRACTIONAL DISTILLATION METHOD - Siti Aisyah dan Masril Chan (Department of Agroindustrial Technology, Bogor Agricultural University, 2011)
ABSTRACTPatchouly oil have the biggest value in the total Indonesian essential oil export. The aim of this research is to separate patchouli alcohol from patchouly oil used fractionation distillation methode. The results showed that fractionation distillation of patchouli oil with fraction 0, 1 and 2 has met SNI 06-2385-2006 inquiry. The treatment of low pressure in process will be increase patchouli alcohol. Except that, destilate process the fractionation patchouli oil at low temperature content residu patchouli alcohol, specific gravity, refractive index and optical rotation has met SNI 06-2385-2006.Keywords: patchouli oil, distillations, fractionation